Single Transsacral Screw and Nut Stabilization of Bilateral Sacroiliac Luxation in 20 Cats - Pratesi, Andrea; Grierson, James M.; Moores, Andrew P. (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objective This article aims to describe the use of a single transsacral screw and nut in a cohort of cats with bilateral sacroiliac (SI) luxation and document its radiographic and clinical outcome.Methods Medical records and radiographic studies of cats with bilateral SI luxation managed with a transsacral screw and nut stabilization were reviewed. Short-term follow-up included clinical examination and radiographs. Long-term follow-up was via owner questionnaire.Results Twenty consecutive cats with bilateral SI luxation were included. Six cats (35%) had additional musculoskeletal injuries that required stabilization. Luxations were stabilized with a single 2.7 cortical self-tapping transsacral screw and nylon nut (a metallic nut was used in one case). Postoperative radiographs confirmed SI reduction in all cats and a mean pelvic canal width ratio of 1.21 (a ratio of ≥1.1 was considered optimal). All cats available at follow-up examination were able to walk without signs of discomfort. Evaluation of follow-up radiographs showed maintenance of SI reduction and slight reduction of mean pelvic canal width ratio (1.18). Fourteen owner questionnaires were returned (median follow-up time of 40 months): nine cats were deemed to have normal activity and five cats were reported to have slight to mild reduced ability to jump or run.Clinical Significance The use of transsacral screw and nut stabilization of bilateral SI luxation in cats is a successful, repeatable and safe technique.
Keywords: bilateral SI luxation; cats; traumatology; transsacral screw; questionnaire